Fluoroxysulphate: A Powerful New Oxiadant, Kinetic Aspects - Agarwal , G.L.; Chourasia, Rajesh; Lari, G.A.; Agarwal, Priti (Asian Journal of Chemistry, 2010)
In this review we highlight the recent work on the reaction chemistry of aqueous fluoroxysulphate.